2010
DOI: 10.1152/jn.00761.2010
|View full text |Cite
|
Sign up to set email alerts
|

Learning on Multiple Timescales in Smooth Pursuit Eye Movements

Abstract: We commonly think of motor learning as a gradual process that makes small, adaptive steps in a consistent direction. We now report evidence that learning in pursuit eye movements could start with large, transient short-term alterations that stoke a more gradual long-term process. Monkeys tracked a target that started moving horizontally or vertically. After 250 ms of motion had produced a preinstruction eye velocity close to target velocity, an orthogonal component of target motion created an instructive chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 45 publications
(29 reference statements)
3
57
0
Order By: Relevance
“…During oculomotor learning, a spike in a climbing fiber on one trial is associated with a suppression of firing in its Purkinje cell target on the next trial (Kimpo et al, 2014; Medina and Lisberger, 2008; Yang and Lisberger, 2010, 2014). The temporal precision of this single-trial plasticity reported in vivo had appeared to be significantly less than what we found at the PF-to-PC synapses in vitro (hundreds of milliseconds vs. tens of milliseconds).…”
Section: Resultsmentioning
confidence: 99%
“…During oculomotor learning, a spike in a climbing fiber on one trial is associated with a suppression of firing in its Purkinje cell target on the next trial (Kimpo et al, 2014; Medina and Lisberger, 2008; Yang and Lisberger, 2010, 2014). The temporal precision of this single-trial plasticity reported in vivo had appeared to be significantly less than what we found at the PF-to-PC synapses in vitro (hundreds of milliseconds vs. tens of milliseconds).…”
Section: Resultsmentioning
confidence: 99%
“…We subjected monkeys to tracking conditions that cause a learned change in the direction of pursuit eye movements (Medina et al, 2005; Yang and Lisberger, 2010) under different reward conditions. The schematic at the top of Figure 8 illustrates the configuration of the “learning” and “probe” trials used for these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that motor learning occurs on multiple time scales (Lee and Schweighofer, 2009; Ethier et al, 2008; Smith et al, 2006), including situations where the behavior on a given trial reflects the instruction provided on the previous trial (Yang and Lisberger, 2010). To measure the relative contributions of single-trial versus longer-term learning processes to the behavioral and neural changes reported here, we sorted learning trials based on the identity of the immediately preceding trial.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the cerebellum could act independently in learning motor timing, or inputs from the FEF SEM could contribute to the temporal sparseness of the granule cell population in a way that is enhanced by learning in the FEF SEM . Recent work also has highlighted the possibility that learning occurs on different time scales (Lee and Schweighofer, 2009; Ethier et al, 2008; Smith et al, 2006; Yang and Lisberger, 2010) with the possibility of very rapid short term learning in the cerebellar cortex as a prelude to slower, longer-term changes in the FEF SEM .…”
Section: Discussionmentioning
confidence: 99%